Ultrathin Ti-Deficient TiO2 Nanosheets with Pt Single Atoms Enable Efficient Photocatalytic Nitrate Reduction to Ammonia - Jung, Hayoon; Cha, Gihoon; Kim, Hyesung; Will, Johannes; Zhou, Xin; Spiecker, Erdmann; Breu, Josef; Schmuki, Patrik (Journal of the American Chemical Society, 2025)
Ti-deficient TiO2 nanosheets derived from lepidocrocite-type titanate delamination show a p-type conductivity with a band gap widened by the quantum confinement effect to 3.7 eV. This shift in the extended band positions─and thus in the electron transfer level─allows a direct photocatalytic nitrate reduction to ammonia without the use of any hole scavengers; this in contrast to classic TiO2. The deposition of Pt single atoms as cocatalysts onto the nanosheets significantly enhances the activity and selectivity toward ammonia, which outperforms classic Pt nanoparticles used as cocatalyst. The present study therefore reports not only on the unique photocatalytic properties of these Ti-deficient TiO2 nanosheets but also on the beneficial use of the modified electronic properties that enable entirely novel applications, such as the technologically highly important reduction of nitrate to ammonia.
CRIS-Team Scopus Importer:2025-03-28